Representation Of Feminism In Disney Brave Film - Merdeka, Pijar Hatinurani (EDUPEDIA Publisher, 2023)
This research was conducted to find out how the representation of women's feminism is shown in the film Brave. Brave is an animated princess-themed film created by Pixar Animation Studio and Walt Disney Pictures. This type of research is descriptive qualitative using Vladimir Propp's narrative analysis method. The subject of this research is the film Brave which is seen from its narrative structure. Meanwhile, the research object to be analyzed is the representation of women's feminism. the purpose of this study is to find out how the representation of women's feminism is shown in the film Brave. The conclusion of this study is that the Brave film narrative tries to present elements of feminism by breaking female stereotypes. However, this film failed to break the working pattern of the patriarchal system. The film's narrative actually marginalizes women by repeating, affirming, and even justifying stereotypes of women in the film's text, through the selection of conflicts, story development, and the climax at the end of the story. Brave narrates stereotypes about women's work, character, behavior, way of thinking, sexuality, and appearance, as well as their relationship with men. These stereotypes appear in the characters Merida and Elinor.